Participation in a randomised controlled feasibility study of a complex intervention for the management of the Respiratory Symptom Distress Cluster in lung cancer: patient, carer and research staff views - Bailey, Christopher; Ellis-Hill, Caroline; Molassiotis, A.; Mackereth, P.; Lloyd-Williams, M.; Yorke, J. (Wiley, 2017)
This paper reports finding from a nested qualitative study designed to elicit the views and perceptions of those who participated in a randomised controlled feasibility trial testing a non‐pharmacological intervention, Respiratory Distress Symptom Intervention (RDSI), for the management of the breathlessness–cough–fatigue symptom cluster in lung cancer. Semi‐structured interviews were conducted with 11 lung cancer patients, three caregivers and seven researchers involved in recruitment, consent, RDSI training and delivery and participant follow‐up. Thematic analysis identified key considerations including: the importance of informed consent emphasising commitment to completion of paperwork and raising awareness of potential sensitivities relating to content of questionnaires; ensuring screening for the presence of symptoms reflects the language used by patients; appreciation of the commitment required from participants to learn intervention techniques and embed them as part of everyday life; conduct of interviews with patients who decline to participate; and conduct of serial interviews with those receiving RDSI to further inform its routine implementation into clinical practice. This study will inform the development of a fully powered follow‐on trial testing the hypothesis that RDSI plus usual care is superior to usual care alone in the effective management of this symptom cluster in lung cancer.